Overview of Community Knowledge on Hepatitis C Disease in the Pulo Gebang Public Housing Area, Cakung, East Jakarta - Elisya, Yetri; Aulia, Septi Nurul; Junaedi; KA , Nanang (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Hepatitis C is a virus infection of the liver that can lead to severe complications, including cirrhosis and hepatocellular carcinoma. Despite the existence of established principles, there remains a prevalence of erroneous comprehension within the populace regarding this subject. The possession of knowledge by the general population is of paramount importance in the efforts to prevent and control hepatitis C. The objective of this study is to ascertain the level of knowledge of the residents of Pulo Gebang Residential Complex in Cakung, Jakarta Timur, with regard to hepatitis C. The nature of the research is quantitative descriptive, with a quota sampling technique employed to determine the sample size. The total number of respondents included in the study was 96. The collection of data was achieved through the utilisation of a questionnaire. The findings indicate that the majority of respondents are female (76%), aged between 18 and 59 years (83.3%), have a secondary education (50.1%), and are not employed (56.2%). The level of knowledge of the respondents was categorised as follows: 47.9% of respondents demonstrated a satisfactory level of knowledge, 33.3% demonstrated an adequate level of knowledge, and 18.8% demonstrated an insufficient level of knowledge. Nevertheless, a misperception remains regarding the manner of transmission and the existence of a vaccine. It is imperative that education on the subject is sustained in order to enhance public awareness and understanding of hepatitis C.